Research of Application of Model-free Adaptive Control Strategy in DVR - CHEN Fei; HAN Xu-shan (Gong-kuang zidonghua, 2010)
In view of problems that traditional feed forward control method of DVR has steady-state error and is insensitive to disturbance of power grid, the paper proposed a design scheme of DVR system based on model-free adaptive control strategy. The scheme needs not build mathematic model of DVR system, it only accords to instantaneous voltage of load and input voltage of controlled system to extract effective data which are processed by model-free adaptive controller, then the processed data controls inverter to produce compensation voltage which is superimposed in power grid after harmonic wave is filtered by LC filter, so as to ensure reliability of voltage of load side. The simulation result proved correctness and feasibility of the scheme.